PENINGKATAN HAFALAN JUZ 30 ANAK USIA DINI MELALUI METODE TALAQQI–REPETISI BERBASIS PERMAINAN - Dewi Sri Hening Trisna; Siti Maisaroh (STKIP Subang, 2025)
This classroom action research investigated the effectiveness of a play-based talaqqi-repetition method in improving Juz 30 memorization among 13 kindergarten students at TK Islam Duta Ananda, Sleman. Using the Kemmis & McTaggart model across two cycles, the study addressed common problems in early childhood tahfidz education: monotonous instruction leading to boredom, poor retention, and low confidence. Results demonstrated substantial improvement, with average memorization scores rising from 2.38 (pre-cycle) to 4.12 (cycle 2), and classical mastery increasing from 15.38% to 92.31%. Both qualitative and quantitative data confirmed that integrating play-based strategies with traditional talaqqi-repetition methods significantly enhanced focus, motivation, retention, and emotional engagement in children aged 5-6 years, aligning with research showing multisensory approaches strengthen learning outcomes in early childhood education.